Factors Influencing Undergraduate Music Majors' Collegiate Decisions - Juchniewicz, Jay; Ward, Jeffrey (My University, 2024)
The purpose of this study was to examine factors influencing undergraduate music majors’ collegiate decisions. Results indicate the strong influence of on-campus musical activities and personal interactions with university music faculty on collegiate selection, including Summer Music Camps, in-person or virtual lessons, and interactions with faculty via social media platforms.
Presented at the 2024 Biennial NAfME Music Research and Teacher Education Conference
Keywords: Undergraduate students; Music Majors; College; Music education